Transfer Pricing Memoderasi Profitabilitas, Kepemilikan Asing, dan Komite Audit Terhadap Tax Avoidance - Wijayanti, Nur; Ayem, Sri (E-Jurnal Akuntansi; Vol 32 No 7 (2022)DO - 10.24843/EJA.2022.v32.i07.p19, 2022)
This study aims to obtain empirical evidence of the effect of profitability, salt ownership and audit committee on tax avoidance, and to use transfer pricing as a moderating variable. The research sample is manufacturing companies listed on the Indonesia Stock Exchange in 2016 – 2020. The analysis used is multiple linear regression and interaction test (MRA). The test results show that profitability has a positive effect on tax avoidance, while foreign ownership and audit committees have a negative effect on tax avoidance. Transfer pricing is not able to moderate the effect of profitability and foreign ownership on tax avoidance. Meanwhile, transfer pricing is able to weaken the influence of the audit committee on tax avoidance. Keywords: Profitability; Foreign Ownership; Audit Committee; Tax Avoidance; Transfer Pricing.